Advanced prediction to facilitate biocontrol of the mealybug Rastrococcus iceryoides (Hemiptera: Pseudococcidae) in organic mango (Anacardiaceae) orchards. Issue 1 (18th September 2017) - Gujjar, Nagalakshmi R; Verghese, Abraham; Suresh, Devi Thangam; Mouly, Rakshitha; Joshi, Sunil
Abstract: Predicting mango mealybug, Rastrococcus iceryoides (Green) (Hemiptera: Pseudococcidae), populations in an organic mango ( Mangiferaindica Linnaeus; Anacardiaceae) ecosystem well in advance with reasonable accuracy, will facilitate biological control. In this study, an attempt was made to predict the population of mango mealybug using abiotic weather parameters as independent variables. The study was conducted at the Indian Council of Agricultural Research – Indian Institute of Horticultural Research, Bengaluru, India (12°8'N; 77°35'E). Among the abiotic variables, maximum temperature was found relevant for predicting the population of the mealybug based on significant correlations. It was found that a prediction model using maximum temperature as independent variable with R 2 is most ideal. This prediction model, when considered three to four weeks in advance of an infestation, could help farmers to gear up with biological control.